Differentially Regulated Apolipoproteins and Lipid Profiles as Novel Biomarkers for Polypoidal Choroidal Vasculopathy and Neovascular Age-Related Macular Degeneration - Zhang, Xinyuan; Qiu, Bingjie; Gong, Zhizhong; Chen, Xiaosi; Wang, Yanhong; Nie, Yao (Frontiers in Endocrinology, 2022)
Lipid dyshomeostasis has been implicated in the pathogenesis of various retinal and choroidal vascular diseases. This study aims to investigate whether apolipoprotein (apo) mediated differential regulation of lipid metabolism contributes to the phenotypes of polypoidal choroidal vasculopathy (PCV) and neovascular age-related macular degeneration (nAMD). This study involved 148 subjects including 53 patients with PCV, 44 patients with nAMD, and 51 age-, sex-matched subjects with normal fundus controls. Routine blood biochemistry profile was evaluated. Apolipoproteins was estimated by Luminex technology. After controlling for age, gender, body mass index, duration of hypertension and type 2 diabetes mellitus, apoB/ non-high density lipoprotein cholesterol (HDL-C) (p=0.015) was an independent risk factor for nAMD, apoB was an independent risk factor for PCV(p=0.011), compared with control. Low-density lipoprotein cholesterol (LDL-C) was significantly higher in patients with PCV when compared with nAMD (p=0.037). Furthermore, apoB/non-HDL, LDL-C, triglycerides and were significantly correlated with the pathogenesis of subgroups of PCV and nAMD. We concluded that lipid profiles and apos are differential regulated in PCV, nAMD and their subtypes, indicating different pathogenicity contributed to the different phenotypes of PCV and nAMD. Non-pachy PCV shares pathological similarities with nAMD, which is highly correlated with age-related atherosclerosis.